Perbandingan Sistem Struktur Dan Biaya Pelat Lantai Metode Precast Half Slab Dan Metode Konvensional - Mochamad Romi; Iskandar Romey Sitompul; Rian Tri Komara Iriana (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
The increase in construction of building need a more efficient of slab construction method. The conventional formwork is considered uneconomical because expensive cost of materialsand labor, longer construction time, and producing significant amount waste of wooden formwork. Currently, green construction have been implemented in building projects such ashalf slab. Half slab method is divided into concrete precast and in-situ concrete works. This research aims to analyze the comparison of precast half slab and conventional method aboutstructural system and cost of construction. A computer program called Safe12 used to define precast half slab and conventional slab model. Safe12 output analysis used to calculatebending moment and shear strength. The cost estimated is according to works volume and the unit price analysis. Based on the analysis results, it observed that bending moment strengthfor precast half slab 28.532 KNm and conventional slab 25.181 KNm, and both method have equally shear strength 84.246 KN. The cost of construction for precast half slab Rp.5,712,441,933.442 and conventional slab Rp. 7,241,288,801.897. The indicates that structural system for both method have similar strength in construction, and cost of construction for precast half slab is more efficient 21,113% than conventional slab cost.Keywords: precast half slab, conventional slab, construction, Safe12